Preputial reconstruction and urethrostomy after subtotal penile amputation in a dog - KATAYAMA, M; SEKI, T; TAKAHIRA, A (Journal of the Hellenic Veterinary Medical Society, 2018)
A 7-year-old, 4.2-kg intact male toy poodle was presented to the referring veterinarian with a persistent penile erection and secondary paraphimosis. A full-thickness longitudinal incision was made in the prepuce to release strangulation by the preputial orifice. Castration was also performed. However, the persistent erection did not resolve, which suggested idiopathic priapism. Although prescrotal or scrotal urethrostomy was considered, these procedures commonly have complications, such as severe hemorrhage, stricture of the urethral opening, urine scalding, and abnormal cosmetic appearance. Therefore, preputial reconstruction and urethrostomy were performed following amputation of the penis. A V-Y skin plasty was performed to retract the prepuce caudally. Two triangles of preputial skin at the middle of the prepuce were removed to shorten the prepuce. A 6-Fr catheter was kept in place for 9 days after surgery to prevent stricture formation and to divert urine during initial healing. After surgery, the dog was able to urinate through the natural preputial orifice, showing no urine scalding of the urethrostomy site. Six months after surgery, nomajor complications were observed. The owner was satisfied with the functional and cosmetic outcome.